Retinal neuronal cell loss prevents abnormal retinal vascular growth in a rat model of retinopathy of prematurity. (March 2018) - Nakano, Ayuki; Asano, Daiki; Kondo, Ryo; Mori, Asami; Arima, Shiho; Ushikubo, Hiroko; Sakamoto, Kenji; Nagamitsu, Tohru; Ishii, Kunio; Nakahara, Tsutomu
Abstract: A short-term blockade of the vascular endothelial growth factor (VEGF)-mediated pathway in neonatal rats results in formation of severe retinopathy of prematurity (ROP)-like retinal blood vessels. The present study aimed to examine the role of retinal neurons in the formation of abnormal retinal blood vessels. Newborn rats were treated subcutaneously with the VEGF receptor tyrosine kinase inhibitor, KRN633 (10 mg/kg), or its vehicle (0.5% methylcellulose in water) on postnatal day (P) 7 and P8. To induce excitotoxic loss of retinal neurons, N -methyl-D-aspartic acid (NMDA) was injected into the vitreous chamber of the eye on P9. Changes in retinal morphology, blood vessels, and proliferative status of vascular cells were evaluated on P11 and P14. The number of cells in the ganglion cell layer and the thickness of the inner plexiform layer and inner nuclear layer were significantly decreased 2 days (P11) after NMDA treatment. The pattern and degree of NMDA-induced changes in retinal morphology were similar between vehicle-treated (control) and KRN633-treated (ROP) rats. In ROP rats, increases in the density of capillaries, the tortuosity index of arteries, and the proliferating vascular cells were observed on P14. The expansion of the endothelial cell network was prevented, and the capillary density and the number of proliferating cells were reduced in NMDA-treated retinas of both control and ROP rats. Following NMDA-induced neuronal cell loss, no ROP-like blood vessels were observed in the retinas. These results suggest that retinal neurons play an important role in the formation of normal and ROP-like retinal blood vessels. Highlights: Short-term VEGF inhibition interrupts retinal vascular development in rats. The impaired vascular development induces retinal hypoxia and VEGF expression. The enhanced VEGF-VEGFR2 pathway induces abnormal vascular formation. Excitotoxic loss of retinal neurons prevents abnormal vascular formation. Retinal neurons play an important role in abnormal retinal vascular formation.